2019
DOI: 10.1097/hp.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Recent Epidemiologic Studies and the Linear No-Threshold Model For Radiation Protection—Considerations Regarding NCRP Commentary 27

Abstract: National Council on Radiation Protection and Measurements Commentary 27 examines recent epidemiologic data primarily from low-dose or low dose-rate studies of low linear-energy-transfer radiation and cancer to assess whether they support the linear no-threshold model as used in radiation protection. The commentary provides a critical review of low-dose or low dose-rate studies, most published within the last 10 y, that are applicable to current occupational, environmental, and medical radiation exposures. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 77 publications
2
42
0
Order By: Relevance
“…First, the range of radiation levels analyzed in the NCRP's study was at least several folds higher (and in many cases even several orders higher) than in our study. Second, even in those relatively high levels, no significant association was found between radiation and several site-specific cancers, among which are gender-dependent cancers (cervix, breast, and prostate) and leukemia 10 -the results that are in fact consistent with ours. Furthermore, the NCRP's study did not relate to cancers in which we did find a significant negative correlation of mortality rates with background radiation levels (i.e., pancreas, colon, brain, and bladder).…”
Section: Discussionsupporting
confidence: 88%
“…First, the range of radiation levels analyzed in the NCRP's study was at least several folds higher (and in many cases even several orders higher) than in our study. Second, even in those relatively high levels, no significant association was found between radiation and several site-specific cancers, among which are gender-dependent cancers (cervix, breast, and prostate) and leukemia 10 -the results that are in fact consistent with ours. Furthermore, the NCRP's study did not relate to cancers in which we did find a significant negative correlation of mortality rates with background radiation levels (i.e., pancreas, colon, brain, and bladder).…”
Section: Discussionsupporting
confidence: 88%
“…Patients were divided into five groups according to age at the time of the examination: less than 1 year old (< 1), one to 5 years old (1-5), six to 10 years old (6-10), 11 to 15 years old (11)(12)(13)(14)(15), and 16 to 17 years old (16,17).…”
Section: Methodsmentioning
confidence: 99%
“…Tissue weighting factors, based on population-averaged values, as used in the calculation of E, make E no more a reliable indicator of individual detriment than population-based organ-specific factors [10]. In the current paradigm of radiation protection, the known relationship between dose and risk at higher radiation dose is assumed to extrapolate linearly to that at lower dose, and children are considered to be at greater risk of developing radiation-induced tumors due to their life expectancy and higher radiosensitivity of select tissues [7,[10][11][12]. The basis for the belief of relatively higher risk for children demonstrated in a report by the National Research Council is challenged by some in light of their view that the risks at low radiation doses such as those incurred during medical imaging procedures are not unequivocally supported by current epidemiological data [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the linear non-threshold hypothesis (when applied at the population level) suggests that the likelihood of developing cancer increases linearly with radiation dose, and there is as such no threshold below which carcinogenesis does not occur (51). A recent review of the epidemiological evidence on radiation expose and cancer risk supported the continued use of the linear no-threshold model for the purpose of radiation protection, although the authors acknowledged that the possible risk associated with very low doses of radiation is small and uncertain (1). In a pooled analysis of nine cohort studies of childhood low dose radiation exposures (including children who received therapeutic radiation for cancer/benign diseases and survivors of the atomic bombing in Japan), the authors concluded that their analyses reaffirmed the linearity of the dose-response relationship between low-dose radiation exposure and thyroid cancer (53).…”
Section: Clinical Guidelines and The International Commission On Radimentioning
confidence: 99%
“…Dental x-rays constitute a common source of exposure to ionizing radiation, a known human carcinogen, in the general population. Although the dose of radiation associated with dental radiography is low, there is considered to be no threshold below which exposure to ionizing radiation is completely without risk (1), and patients are likely to be exposed to dental x-rays on multiple occasions over many years. Given this high life-time prevalence and frequency of exposure, even a small associated increase in cancer risk would be of considerable public health importance.…”
Section: Introductionmentioning
confidence: 99%